Iowa Birdline update, August 29, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for August 29, 1988. Highlights of the update include several excellent sightings from Forneys Lake, including six Ibis species, 162 Great Blue Herons, 58 Great Egrets, 14 Snowy Egrets, 3 American Avocets, 2 Bald Eagles, Ring-billed Gulls, and Franklin's Gulls. Also abundant during the week were Warblers, with 14 species seen in central Iowa and 7 species seen in the Iowa City area. Epson - sheet feed/flatbed